Internalisasi nilai etika profesi guru dalam membangun relasi pendidikan humanis - Nisa’, Khoirun (Maliki Interdisciplinary Journal, 2026)
This study aims to examine the role of teachers’ professional ethics in fostering humanistic education through the internalization of ethical values, strengthening teacher-student relationships, and transforming learning practices. The study employs a literature review approach by analyzing relevant academic sources. The findings indicate that key ethical values such as justice, empathy, responsibility, and respect for human dignity play a crucial role in creating an inclusive and meaningful learning environment. Furthermore, humanistic relationships built through dialogic communication and empathetic attitudes significantly enhance students’ motivation and engagement. The transformation from teacher-centered to student-centered learning also contributes to the realization of humanistic education, despite challenges such as administrative demands and technological developments. Therefore, strengthening teachers’ professional ethics is essential to achieve optimal humanistic educational outcomes.